THE ROLE OF THE GOVERNMENT IN THE PROTECTION OF HEALTH WORKERS DURING THE COVID-19 PANDEMIC - Leonard, Tommy; Pakpahan, Elvira Fitriyani (UNISSULA, 2022)
This research aims to identify and analyze accountability in protecting the rights of health workers and complement each other in creating a balance of rights and obligations through preventive and repressive efforts. In this paper using normative juridical research methods and analyzed using qualitative data. The resulting research results state that legal protection for the safety of health workers due to the Covid-19 pandemic has not been implemented properly as mandated in laws and regulations, in carrying out the rights of health workers during the Covid-19 pandemic they are still neglected and have not been fulfilled. Therefore, the role and responsibility of the government is urgently needed to fulfill the rights of health workers as the frontline in handling the spread of Covid-19 in Indonesia.